Kemampuan Mengajar Guru Tamatan IKIP Ujung Pandang Pada Berbagai Jenis dan Jenjang Pendidikan Di Daerah Sulawesi Selatan - H. Sahabuddin (Universitas Negeri Malang, 2016)
The low achievement of the students in South Sulawesi is due to their limited time for study rather than to the low teaching performance of the teachers as products of IKIP Ujung Pandang. This fact is one of the results of a descriptive survey conducted in 5 kabupatens, using 227 teachers, 19 school principals, 5 KAKANDEP and 748 secondary school students as respondents. This sudy also reveals that the graduates of IKIP Ujung Pandang are in general qualified teachers and that they are in the process of becoming professional teachers.